2019
DOI: 10.1111/cod.13221
|View full text |Cite
|
Sign up to set email alerts
|

Methylisothiazolinone allergic contact dermatitis: Assessment of relapses in 139 patients after avoidance advice

Abstract: Background Methylisothiazolinone (MI) is a preservative that is responsible for an epidemic of allergic contact dermatitis (ACD). Few studies have been published on the prognosis of patients with MI‐induced ACD. Objectives To evaluate relapses of MI‐induced ACD and difficulties in avoiding MI in patients who had received avoidance advice. Methods A retrospective study of patients with MI‐induced ACD diagnosed in two specialized dermato‐allergology units between 2010 and 2015 was performed. The median follow‐up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
9
0
4
Order By: Relevance
“…However, a long-term follow-up was missing, and relapses might be expected due to new exposure to isothiazolinone-containing rinse-off cosmetics, incomplete labelling of some products, and hidden sources, as previously reported. 67 In 2018, the Committee for Registration, Evaluation, Authorisation, and Restriction of Chemicals (REACH) in the European Union decided that industrial products, such as paints and detergents, must bear the warning, "Contains methylisothiazolinone. May cause an allergic skin reaction", when they contain more than 15 ppm MI.…”
Section: Discussionmentioning
confidence: 99%
“…However, a long-term follow-up was missing, and relapses might be expected due to new exposure to isothiazolinone-containing rinse-off cosmetics, incomplete labelling of some products, and hidden sources, as previously reported. 67 In 2018, the Committee for Registration, Evaluation, Authorisation, and Restriction of Chemicals (REACH) in the European Union decided that industrial products, such as paints and detergents, must bear the warning, "Contains methylisothiazolinone. May cause an allergic skin reaction", when they contain more than 15 ppm MI.…”
Section: Discussionmentioning
confidence: 99%
“…Bouschon i wsp. zwracają uwagę na złe rokowanie u pacjentów z alergicznym kontaktowym zapaleniem skóry wywołanym izotiazolinami [23]. U 64% z 139 chorych wystąpiły nawroty, w tym u 18% o ciężkim przebiegu [23].…”
Section: Omówienieunclassified
“…Szkodliwe działanie wykazywały nie tylko kosmetyki pozostawiane na skórze, ale i spłukiwane. Te ostatnie były odpowiedzialne za 27% nawrotów alergicznego kontaktowego zapalenia skóry [23].…”
Section: Omówienieunclassified
See 1 more Smart Citation
“…The beneficial impact of an adequate diagnosis of contact allergy-in this case, to MI-is illustrated by a study evaluating the QoL before diagnosis and at 3-months follow-up after diagnosis of MI contact allergy, finding a highly significant improvement [115]. However, particularly with more long-term follow-up, relapses despite counselling are not infrequent and mostly related to hidden sources of MI, the lack of labelling on industrial products, the complexity of cosmetic labelling, and remembering the name of the allergen [116]. A Thai study found that widespread dermatitis, seen in 20.2% of 3201 patients, demonstrated that preservatives were the significant offending allergens, especially MCI/MI and MI alone [117].…”
Section: Preservativesmentioning
confidence: 97%